Rwanda : Sixth Review Under the Policy Support Instrument and Request for Extension of the Policy Support Instrument-Staff Report; Press Release. (IMF Staff Country Reports; Country Report ;, 2013)
Rwanda has responded to lower aid by tightening policies and drawing on its foreign reserves to cushion the impact on the economy. Economic activity has been resilient despite lower aid inflows. The agreed framework for the FY2013/14 budget is in line with Policy Support Instrument (PSI) objectives. The government's intention to develop a comprehensive plan for enhancing domestic revenue mobilization over the medium term is timely. Rwanda's new poverty reduction strategy (EDPRS2) and the commitment to tighten the monetary stance while allowing greater exchange rate flexibility is encouraging.